THE LEGALITY OF MURABAHAH CONTRACTS SYSTEM IN ISLAMIC FINANCING INSTITUTIONS: An Analysis of Muḥammad Bin Ṣāliḥ Al-Uṡaimīn‘s Thought - Hakim, Ahmad Luqman; Munandar, Irfa (JURISTA: Jurnal Hukum dan Keadilan, 2023)
Uṡaimīn regarding the legality of sales and purchase agreements in financial institutions. The question emerges to what extent the propositions and patterns of legal reasoning used by Muḥammad bin Ṣāliḥ al-Uṡaimīn? This research was conducted using qualitative methods, the type of research is descriptive analysis. The results of the research show that according to Muḥammad bin Ṣāliḥ al-Uṡaimīn the sale and purchase agreement through a financing institution or other financing company is invalid and void. The proposition used by Muḥammad bin Ṣāliḥ al-Uṡaimīn is QS. Al-Baqarah [2] verse 275 which states the halal nature of buying and selling and the prohibition of usury. Another argument refers to the hadith history from Abu Dawud, Al-Tirmizi, Al-Nasa'i, Ibn Majah, and Imam Ahmad who both narrated the prohibition of the Prophet Muhammad from selling an item that he did not already own. From the arguments he used, it was discovered that the istinbath method he used was the ta'liliyyah method, namely a method of legal discovery and reasoning whose main focus is to see whether there is legal illat in the problem being studied. In the case of buying and selling at a finance company, Muḥammad bin Ṣāliḥ al-Uṡaimīn discovered and saw the practice of usury in it, so that usury became illat or the legal reason for prohibiting this practice.